Reply to Otter et al. Comment on “Bernard et al. Association between Urinary Metabolites and the Exposure of Intensive Care Newborns to Plasticizers of Medical Devices Used for Their Care Management. Metabolites 2021, 11, 252” - Lise Bernard; Yassine Bouattour; Morgane Masse; Benoît Boeuf; Bertrand Decaudin; Stéphanie Genay; Céline Lambert; Emmanuel Moreau; Bruno Pereira; Jérémy Pinguet; Damien Richard; Valérie Sautou; et al. (Metabolites, 2021)
The comments written by R. Otter et al. [...]